Peningkatan Hasil dan Aktivitas Belajar Siswa Materi Yesus Mengajarkan Pengampunan Melalui Model Pembelajaran Discovery Learning di Kelas V SDS Santa Lusia Siborongborng - Saut Beres Purba (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The aim of this research is to improve the activities and learning outcomes of Catholic religious education and character with the aim of learning to understand Jesus who taught forgiveness and called sinners and Jesus obeyed God, so that they are able to realize their faith in everyday life through the Discovery Learning learning model. This research is classroom action research involving 32 fifth grade students at Santa Lusia Siborongborong Private Elementary School in the 2023/2024 academic year. Actions are carried out in two learning cycles. Data was collected using observation guidelines, formative assessments in each cycle, and analyzed descriptively. The results of the research showed that in cycle I the average percentage of student learning activities was 80% with classical completeness of cognitive learning outcomes obtained at 96.77%, with an average learning outcome score of 84. In cycle II the average percentage of student learning activities was 90.63% with classical completeness of cognitive learning outcomes of 93%, with an average learning outcome score of 100. Thus, the application of the Discovery Learning learning model can increase student activity and learning outcomes.